Exopolysaccharides synthesized by thermophilic microorganisms isolated from bulgarian hot springs - (:unkn) unknown (Bulgarian Society for Microbiology (Union of Scientists in Bulgaria), 2018)
High temperature in thermophilic niches determines unusual metabolic processes based on an abil-ity of thermophilic microorganisms to synthesize unusual compounds. One of the strategies for active growth of this type of extremophiles is a synthesis of exopolysaccharides (EPSs). EPSs from thermophiles are characterized by unknown before composition of their molecules and correspondingly unusual phys-ic-chemical properties. Several thermophilic EPS producers were isolated from Bulgarian hot springs and three of them belonging to different genera were chosen for further work, namely Geobacillus tepidamans V264, Aeribacillus pallidus 418, and Brevibacillus thermoruber 423. Cultivation medium and conditions were optimized for each EPS producer. Influence of agitation and aeration rates on the bacterial growth and polymer synthesis were investigated in laboratory fermentors for some of them. Biosynthesis in continuous cultures revealed low increase of the yield and higher degree of purity of the EPS synthesized by A. pallidus 418. Productivity of one of the strains, B. thermoruber 423 was comparable with that of mesophilic bacteria. Investigations of their molecules revealed unknown before composition, high molecular weight, and thermostability. Physico-chemical analyses of their properties revealed an unique rheology like viscous solutions at low concentrations, good emulsifying properties, stability of emulsions, and good synergism with other hydrocolloids. EPS from G. tepidamans V264 expressed biological activity against cytotoxic compounds, while that from B. thermoruber 423 showed good compatibility with monkey fibroblast cell lines. The demonstrated functional properties and biological activities determine their possible future ap-plications in cosmetics and medicine. © 2018, Bulgarian Society for Microbiology (Union of Scientists in Bulgaria). All rights reserved.
Keywords: Bacterial exopolysaccharides; EPS composi-tion; biotechnologically potential; Polysaccharide production; Thermophilic bacteria